(3GdJNWjW GdHjFi GdeSJOGe ai VhA GdMSGSjI GdHjFjI ddehbY (B: s (3OQGSI MGdI Ebdje HMjQI fGUQ (B/ s - (3eMeO YHOGdYRjR YHOGdHGSW TMGJs; (3HGSfJ gTGe jhSa (B: s; (3eMeO QVG MLGL (B: s ((3GdbGgQI (B: s (3eMeO YHOGdYRjR YHOGdHGSW TMGJ (B: s, 2016)
(3EYJHQJ NWW GdJfejI GdbhejI Cf Ebdje HMjQI fGUQ dg OhQkG MjhjkG ai eSJbHd GdJfejI GdbhejI ai eUQ, fXQkG dCf GdEbdje ef Zfi HGdehGQO GdJfehjI h GdHjFjI GdeJYOOI h JhGLO eNRhf ESJQGJjLi ef GdehGQO GdJfehjI GdZjQ eSJZdI HGdEbdje(B. (3h ai gPG GdHMK Je GbJQGM CMO efGgL GdJNWjW GdHjFi h gh efgL GdMaGX Ydi GdHjFI dEYJHGQg GSH WQb GdJfejI ddJYGed eY NUhUjI Ebdje HMjQI fGUQ h dJYXje GdHYO GdHjFi ai YedjGJ h eQGMd GdJfejI GdeNJdaI h fXQkG dMSGSjI GdefWbI HjFjG aEf WQb h efGgL GdJNWjW GdJbdjOjI dG JfGSH WHjYI efWbI GdOQGSI h ef gfG cGf GSJNOGe efGgL GdJNWjW GdHjFi HGJHGY GOhGJ GdJNWjW ddJYGed eY bVjI GdJfejI GdTGedI ai Gbdje HMjQI fGUQ HTcd eKGdi HMjK jJe JMbjb h JWHjb eYGjjQ GdJfejI GdeSJOGeI h GdYeGQI GdNVQGA ai VhA GdMaGX Ydi GdHjFI PGJ GdWHjYI GdNGUI ai efWbI GdOQGSI h JMbjb GdZQV GdCSGSi ddJfejI ai GdEbdje h gh GdhUhd Edi eLJeYGJ YeQGfjI JfehjI NVQGA eSJOGeI Mhd HMjQI fGUQ h EbdjegG GdJfehi eSJbHdjGs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJNWjW GdEbdjei h GdYeQGfi (B- (3bSe GdJNWjW GdHjFi h GdHfjg GdGSGSjg s
(3UOQ GjVG cbQU eOeLs
Keywords: (3Ebdje HMjQI fGUQs; (3GdJNWjW GdHjFi GdeSJOGes; (3NWW GdJfejI GdbhejIs